PRACTICE EXPERIENCES OF SOUTH AFRICAN SOCIAL WORKERS LIVING WITH DISABILITIES - Zimba, Zibonele France (Social Work/Maatskaplike Werk, 2021)
For more than three decades in the field of social work the focus has been on social workers and persons living with disabilities. The purpose of this article is to present the findings of an empirical study on practice experiences of social workers living with disabilities in South Africa. A qualitative research methodology was used to achieve the objective of the study. Data were collected through semi-structured one-on-one interviews with seven social workers living with disabilities. The findings of the study revealed that social workers with disabilities consider their experiences in practice as both positive and negative. The study also revealed that participants experience challenges in practice.